2022
DOI: 10.1590/1980-220x-reeusp-2021-0333en
|View full text |Cite
|
Sign up to set email alerts
|

Process-based Management aimed at improving health care and financial results

Abstract: The limited resources allocated to the health area and the growing demands require leaders’ qualified and committed performance in hospital management. In this perspective, the objective of this study is to reflect on the management practices that can be applied to hospital facilities to achieve better care and financial results. Among them, process-based management proposes an approach for continuous process improvement to achieve desired results; the method Lean Six Sigma allows identifying and eliminating w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
9

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 19 publications
0
14
0
9
Order By: Relevance
“…From this perspective, Lean methodology adoption makes the use of strategic, tactical and operational indicators crucial, as it requires a clear definition of the objectives and goals to be achieved, with systematic and continuous measurements. Strategic map integration with this methodology enables a systemic view of the institution by identifying weaknesses and points that can be improved, seeking sustainability based on results indicators, with gains in the small, medium and long term ( 7 ) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…From this perspective, Lean methodology adoption makes the use of strategic, tactical and operational indicators crucial, as it requires a clear definition of the objectives and goals to be achieved, with systematic and continuous measurements. Strategic map integration with this methodology enables a systemic view of the institution by identifying weaknesses and points that can be improved, seeking sustainability based on results indicators, with gains in the small, medium and long term ( 7 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies analyzed, three corresponded to review articles ( 11 , 15 , 17 ) , which assessed the Lean tools used in research ( 17 ) , the results after implementing Lean methodology ( 16 ) and its sustainability ( 11 ) . In this integrative review, it was found that the Lean methodology can bring benefits to organizations ( 7 , 15 ) , and is associated with process improvements, waste reduction, increased efficiency and productivity, improvement in service quality ( 13 , 17 - 19 ) , contributing favorably to economic aspects ( 12 , 16 ) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that have analyzed health care in these two types of services have shown some factors that can affect or enhance access to these services, such as priority/rapidity in care and a greater number of referrals to private services, infrastructure problems, lower travel costs and a greater number of visits to the public network ( 22 , 23 ) . In addition, the COVID-19 pandemic has posed a number of challenges for health systems, mainly due to the increase in costs and the number of beds, making it necessary to review management models, access, processes and funding policies ( 24 ) .…”
Section: Discussionmentioning
confidence: 99%